'domesticating' Low Carbon Thermal Technologies: Diversity, Multiplicity and Variability in Older Person, Off Grid Households - Wrapson, W; Devine-Wright, P (Elsevier, 2014)
The uptake of low carbon heating technologies forms an important part of government strategies to reduce carbon emissions. Yet our understanding of why such technologies are adopted and how they are engaged with post-adoption, particularly by older adults living in off-grid areas, is limited. Drawing on a contextualised, socio-technical approach to domestic heating, we present findings from 51 in-depth interviews with a sample of 17 older person households in the South West of England, with ages ranging from 60 to 89 years. Diverse and multiple configurations of heating devices and fuels were found that varied considerably, with some households using five different fuels. The design of the study ensured that approximately half the sample used some form of low carbon thermal technology, such as heat pumps and biomass boilers. Many factors were reported to influence the adoption of low carbon heating; environmental motives were not primary influences and the avoidance of financial risks associated with ‘peak oil’ was expressed. Low carbon thermal technologies were typically integrated into rather than replaced existing heating systems so that valued services provided by conventional technologies could be retained. Implications of the findings for policies to reduce carbon emissions, particularly in older adult, off-grid households, are discussed.
Keywords: Low carbon thermal technologies; Domestication; Older people; Off grid